A case report of cryoablation and electrochemotherapy in kidney cancer. Issue 45 (12th November 2021) - Mastrandrea, Giovanni; Laface, Carmelo; Fazio, Vito; Lopetuso, Marco; Falagario, Gianmarco; Molinari, Pasquale; Ranieri, Girolamo; Gadaleta, Cosmo Damiano
Abstract: Rationale: According to scientific literature, cryoablation (CA) and electrochemotherapy (ECT) have been used for the treatment of small renal masses. However, no data have been published regarding the combination of these techniques as therapy of primary kidney cancers. Therefore, we report the case of an old woman affected by localized kidney cancer and discuss the potential therapeutic application of CA combined with subsequent deep ECT in this setting. Patient concerns: An 85 years-old-woman was evaluated because of a localized kidney cancer. Her background history included long-time hypertension and diabetes mellitus in drug treatment. Diagnoses: In February 2018, the follow-up contrast enhancement computed tomography (ceCT) documented a suspected 18×10 mm metastasis at the lower right lobe of the lung. The ceCT also showed a suspected primary malignancy of 25×18 mm at right kidney. Interventions: The kidney cancer was treated with a two-phase procedure: percutaneous CA and subsequent deep ECT. Outcomes: Patient obtained a complete response according to modified Response Evaluation Criteria in Solid Tumors, without renal function or quality of life impairment. No procedure-related complications were observed. Moreover, a shorter period of hospitalization and convalescence were needed respect to standard surgery. No sign of relapse was observed during follow-up period. Lessons: This combined strategy proved to be safe and effective. Moreover, the application of these blended loco-regional techniques showed several other advantages such as reduced hospitalization and a shorter period of convalescence respect to standard surgery.